FREQUENCY OF CALR GENE MUTATION IN MYELOPROLIFERATIVE NEOPLASMS - Latif, Sana; Khan, Saleem Ahmed; Mahmood, Asad; Robert, Helen Mary; Mahmood, Rafia (Pakistan Armed Forces Medical Journal, 2020)
Objective: To detect the calreticulin gene mutation in myeloproliferative neoplasms and its clinicohaematological correlation. Study Design: Cross sectional study. Place and Duration of Study: Armed Forces Institute of Pathology, from Jun 2017 to Jun 2018. Methodology: A cross sectional study was conducted at Department of Haematology, Armed Forces Institute of Pathology from June 2017 to June 2018. A total of 48 newly diagnosed JAK2V617F patients with negative myeloproliferative neoplasma were enrolled in the study. Clinico-haematologic features were noted. DNA was extracted from bone marrow samples. Molecular analysis was performed for Calreticulin gene by Sanger Sequencing. Results were analysed by using Genetic Analyser HITACHI 3130. Results: Of 48 newly diagnosed JAK2V617F negative myeloproliferative neoplasms patients, 38 were male and 10 were females with M:F ratio of 3.8:1. Mean age was 43.5 years (standard deviation ± 15). 9 (18.8%) were diagnosed as polycythemia vera, 21 (43.8%) as Essential thrombocythemia and 18 (37.5%) as having Primary myelofibrosis. CALR mutation was detected in four (8%) of myeloproliferative neoplasms cases. Out of four CALR positive cases, three were diagnosed to have Primary myelofibrosis while only one had a diagnosis of Essential thrombocythemia. Conclusion: We conclude that CALR mutation was an important molecular marker in JAK2V617F negative patients. Primary myelofibrosis shares a high rate of CALR mutation as compared to polycythemia vera and essential thrombocythemia.